Effect of Age and the Pretest Score on Critical Thinking and Using Concepts Maps in Learning the Skill Scoring of Football for Students - Hussein M. Tuama’a 1 , Mohammed Jabbar Munadi2 , Saif Hadi Minjal 3 , Ayad Rasan Jasim 4 , Heider Sa (Indian Journal of Forensic Medicine & Toxicology, 2020)
The world has witnessed in recent decades rapid developments, Including all areas of life, Prompting thenations to strive to keep abreast of these developments and build their societies, and became human is themain objective of those developments. Through the overlap of a variety of factors, including the methodchosen in the process of teaching and the specific way of teaching, and the characteristics of individuals 2 ofcognitive methods, which vary from individual to other, as a result of individual differences identified, andtook a lot of changes and development These developments were the result of the technological developmentthat covered all fields of life, scientific and practical in general and in particular 3 the sports field. Mindmapping technology has an impact on football scoring skills for first-stage students. Taking notes usingconcepts mapping technology helped the members of the expericoncepts group to plan their ideas fully. Thetechnology used in the current research (concepts maps) has contributed to the development of the dynamicprogram of the members of the expericoncepts group, through the processes of remembering, retaining andreviewing concepts mapping.